Soil Improvement Using the Stone Column Method at the International Port of Tibar, Timor-Leste - Raimundo Gomes; Helmy Darjanto (NAROTAMA UNIVERSITY, Indonesia, 2022)
Stone column (stone column) is one of the soil improvement methods that fall into the category of